Evaluation and comparison of oral function after resection of cancer of the upper gingiva in patients who underwent reconstruction surgery versus those treated with a prosthesis - Yu Ohashi; Kiyoto Shiga; Katsunori Katagiri; Daisuke Saito; Shin-ichi Oikawa; Kodai Tsuchida; Aya Ikeda; Jun Miyaguchi; Takahiro Kusaka; Hiroyuki Yamada (BMC, 2021)
Abstract Background We retrospectively analyzed the articulation, mastication, and swallowing function of patients who underwent reconstruction or used a prosthesis after resection of the upper gingiva. Methods This study included patients who underwent resection of cancer of the upper gingiva from January 2014 to December 2018. Articulatory function was evaluated with Hirose's conversational function evaluation criteria. Mastication function was evaluated with the Yamamoto's occlusion table. Swallowing function was assessed with the MTF (Method of intake, Time, Food) score. Results The mean articulatory function score was 8 points in the Reconstruction Surgery Group (RSG) and 8.8 points in the Prosthesis Group (PG). The mean mastication function score was 2.8 points in the RSG and 3.3 points in the PG. The mean swallowing function score was M3T4F4 in the RSG and M4T4F4.3 in the PG. Conclusions The prosthesis depends on the remaining occlusal support area. Our study suggest that prosthesis is better indication when there is more than one occlusal support area.